Relationship between Parents’ Education and their children’s Academic Achievement - Dr. Muhammad Idris; Dr. Sajjad Hussain; Dr. Nasir Ahmad (Journal of Arts & Social Sciences, 2020)
This study explored the relationship between parents’ education and their children’s academic achievement focusing on father and mother educational level for their children’s academic achievement. Tenth class students of government high schools at District Mardan constituted the population of the study. The study employed systematic random sampling techniques to select students as a sample of the study. Through a self-developed questionnaire, the data were collected from the respondents of the study. The findings of the study revealed that the high education of father and mother positively contributes to their children’s academic achievement. Large co-relation was found between parents’ education and students’ academic achievement. On the basis of the findings, the study recommended introducing adult education programs, awareness campaigns, and the use of social media for community education.